1996
DOI: 10.4319/lo.1996.41.8.1610
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial dynamics in the upper St. Lawrence estuary

Abstract: The distribution of free bacteria in the St. Lawrence estuary was interpreted by means of bacterial fluxes and hydrodynamic residence times, derived from a circulation model, and growth and grazing rates, obtained from cultures. Bacterial abundances decreased exponentially along the salinity gradient, from 3.9 x lo9 liter-' in freshwater to 0.5 x lo9 liter-l at salinity ~20. The rates of growth (0.02-0.08 h-l) and grazing (0.0 l-O.09 h-l) were strongly correlated (r = 0.82), which suggests that bacteria tended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…In such habitats, it is likely that the exchange rate of water is too high to retain the spatial heterogeneity of bacterial community compositions and to adaptively respond to environmental changes. In the St. Lawrence estuary, it has been shown that the rate of changes in bacterial abundance due to horizontal advection and diffusion reflects approximately the same rate of changes due to local growth and grazing loss (Painchaud et al 1996). This situation would correspond to the case with a very high immigration rate in our model, where the bacterial community is predicted not to respond adaptively.…”
Section: Discussionmentioning
confidence: 84%
“…In such habitats, it is likely that the exchange rate of water is too high to retain the spatial heterogeneity of bacterial community compositions and to adaptively respond to environmental changes. In the St. Lawrence estuary, it has been shown that the rate of changes in bacterial abundance due to horizontal advection and diffusion reflects approximately the same rate of changes due to local growth and grazing loss (Painchaud et al 1996). This situation would correspond to the case with a very high immigration rate in our model, where the bacterial community is predicted not to respond adaptively.…”
Section: Discussionmentioning
confidence: 84%
“…Little work has therefore been done on characterising the key fluxes associated with short-term changes in diatom communities. Recently, Painchaud et al (1996) applied a 2-D circulation model to study the effects of biological (i.e. grazing and growth rates) and physical dispersion (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In some applications (e.g., Hecky et al 1993; den Heyer and Kalff 1998) the computation of transport time has been done without specification of the underlying concept used. In other cases (e.g., Andrews and Müller 1983;Hilton et al 1995;Painchaud et al 1996), the underlying concept and computational steps have been based on an idealized circumstance that is constrained by critical assumptions, but the validation (or even recognition) of those assumptions has not always been considered when applied to a real river, lake, or estuary. Given the central importance of the transport time concept and the varied approaches used, we imagined the usefulness of a comment to reprise the advice of Bolin and Rodhe (1973, p. 58): ''To avoid misunderstandings and even erroneous conclusions it is important to introduce precise definitions and to use them with care.''…”
mentioning
confidence: 99%
“…The mechanistic explanation of low plankton abundance in rivers is short residence time relative to population growth rate (Basu and Pick 1996). The occurrence of harmful algal blooms (Bricelj and Lonsdale 1997), distribution of pelagic bacteria (Painchaud et al 1996), export of copepod life stages (Ohman and Wood 1996), partitioning of primary production between macroalgae and phytoplankton (Valiela et al 1997), and variability of dissolved nutrient concentrations (Andrews and Müller 1983) in estuaries and other coastal ecosystems are all strongly influenced by residence time.These examples, all published in Limnology and Oceanography, illustrate that applications of transport time scales are pervasive in biological, hydrologic, and geochemical studies. From a survey of these applications and other literature, we identified flushing time, age, and residence time as three fundamentally different concepts of transport time leading to three different approaches for calculating this scale.…”
mentioning
confidence: 99%
See 1 more Smart Citation